WORKSHOP PENYUSUNAN PEDOMAN PENANAMAN SPIRITUALITAS MARIA HAMBA ALLAH PADA YAYASAN - Paul Suparno (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
The purpose of this workshop was to help Yayasan YSMAK write books about its own spirituality. Yayasan YSMAK wanted to apply the spirituality for all its institutions such as education, orphanage, and polyclinics, but Yayasan had no such books yet. So YSMAK conducted a workshop to write those books. There were 22 teachers and Abdi Kristus nuns who were chosen to be team members for writing those books. A lecturer from Sanata Dharma University, was asked to be a facilitator and editor for the workshop. The workshop had been done during 6 months, from September 2018 to March 2019. The result was that they were able to write 6 books about the MHA spirituality for: kinder garden schools, primary schools, middle schools, vocation school, orphanage, and policlinics. During the workshop the facilitator conducted a retreat and guided them how to write a book on spirituality. He also made correction and edited the books.